Pregnancy and COVID-19, focus on vaccine and pharmacological treatment. (June 2022) - Vitiello, Antonio; Ferrara, Francesco; Zovi, Andrea; Trama, Ugo; Boccellino, Mariarosaria
Abstract: The global pandemic of COVID-19 is currently ongoing. Clinical evidence shows that specific population groups such as the elderly, individuals with comorbidities, and pregnant women may be at increased risk for infection and serious complications. In particular, physiologic changes during pregnancy may be significant on the immune and respiratory systems and progression of COVID-19 disease. Pregnant women are routinely excluded from pre-registration clinical trials, this potentially limits their access to therapies through off-label or compassionate use. Vaccination remains an important pillar of the response to COVID-19, particularly as variants of the virus continue to spread across countries. Growing evidence indicates that COVID-19 mRNA vaccines do not cause pregnancy complications for expectant mothers and their infants. In this brief review, we explore current knowledge about COVID-19 in pregnancy by highlighting current recommendations for vaccination and drug treatments.